Knowledge In Real World Situations: A Diagrammatic Funnel Model - Kong, Christopher; Stevens, Geoff Ruggeri (Journal of Knowledge Management Practice, 2012)
A practical drawing-board style knowledge model is devised which can be used in an evaluative as well as a tracking mode by a wide variety of actors in the stress of real world situations, rather than being elaborate and satisfying theoretical and academic canons. A distinction is made between prior and dynamic knowledge stocks. As an illustration, the model is applied retrospectively to three cases.